2001
DOI: 10.1016/s0960-9822(01)00535-8
|View full text |Cite
|
Sign up to set email alerts
|

Cervical sprouting of corticospinal fibers after thoracic spinal cord injury accompanies shifts in evoked motor responses

Abstract: deficits [1]. Small injuries can result in transient impairments, but the mechanisms of recovery are poorly understood [2]. At the cortical level, rearrangements of the sensory and motor representation maps often parallel recovery [3, 4]. Results and discussion In the sensory system, studies have shown thatAdult female Lewis rats were anesthetized, and their left cortical and subcortical mechanisms contribute to motor cortex was exposed and stimulated by a tungsten map rearrangements [5, 6], but for the motor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
172
1
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 230 publications
(190 citation statements)
references
References 32 publications
13
172
1
2
Order By: Relevance
“…Confirming previous reports (Fouad et al, 2001;Weidner et al, 2001;Raineteau et al, 2002), spinal injury elicited substantial sprouting of the corticospinal tract rostral to the lesion. The trajectories of these collaterals were not limited to regions well supplied with collaterals of the CST in intact rats.…”
Section: Cst Projections To Spn and Spinal Insupporting
confidence: 90%
See 1 more Smart Citation
“…Confirming previous reports (Fouad et al, 2001;Weidner et al, 2001;Raineteau et al, 2002), spinal injury elicited substantial sprouting of the corticospinal tract rostral to the lesion. The trajectories of these collaterals were not limited to regions well supplied with collaterals of the CST in intact rats.…”
Section: Cst Projections To Spn and Spinal Insupporting
confidence: 90%
“…First, after transection, the corticospinal tract of the rat collateralizes abundantly into new regions of the dorsal horn and intermediate zone (Fouad et al, 2001). Second, sprouting corticospinal tract axons (CST) make new connections with somatic interneurons above incomplete spinal lesions.…”
Section: Introduction Rmentioning
confidence: 99%
“…BDNF infused into the rat motor cortex enhanced rostral sprouting, but not regeneration, of corticospinal tract axons injured by thoracic spinal cord dorsal funiculotomies [115]. When we applied this approach after thoracic spinal cord dorsal over-hemisection, the collateral sprouting of corticospinal tract axons and innervation of cervical spinal cord propriospinal interneurons we previously observed [25] was enhanced [116]. Intrathecal infusion of BDNF or pegylated BDNF caudal to thoracic spinal cord transection or contusive injury similarly promoted cholinergic axon sprouting, stimulated hindlimb air-stepping, and improved both hindlimb joint movements and Basso, Beattie, and Bresnahan open field locomotor rating scale scores [117,118].…”
Section: Pharmacological and Gene-delivery Approachesmentioning
confidence: 82%
“…Here, as well, axon collateral sprouting appears to be involved. For example, we found that rat hindlimb corticospinal tract axons axotomized in the thoracic spinal cord dorsal funiculus sprouted axons into the cervical spinal cord gray matter [25]. Associated with this was novel forelimb and trunk muscle activity being evoked by hindlimb motor cortex stimulation.…”
Section: Spontaneous Functional Return and Recovery After Scimentioning
confidence: 94%
“…The recovery of locomotion after partial lesions may depend on multiple cooperative mechanisms that can be regrouped under the general heading of neuroplasticity (Wolpaw and Tennissen, 2001;Nudo, 2006;Rossignol, 2006). After partial SCI, the regeneration of damaged fibers and/or sprouting of undamaged fibers may contribute to recovery (Fouad et al, 2001;Raineteau and Schwab, 2001; Raineteau et al, 2002;Bareyre et al, 2004; Ballermann and Fouad, 2006). Plastic changes within descending pathways could suggest that inputs from the brain and brainstem supplant functions normally performed by the spinal locomotor CPG.…”
Section: Introductionmentioning
confidence: 99%